Inferior Myocardial Infarction and Total AV Block in a Patient with Single Ostium in the Right Sinus of Valsava (A Rare Congenital Coronary Anomaly) - Imam Mahbub Zam Zami (Universitas Airlangga, 2021)
A 51-year-old male suffered from a STEMI inferior and a total AV block. Echocardiography shows hypokinetic wall motion at the inferior and inferoseptal that result in decreased EF. Coronary angiography revealed a single ostium of coronary artery without any stenosis. Cardiac CT revealed a single coronary artery arises from a single ostium from RCC and divided into RCA and LCA. There was an inter-arterial course of proximal RCA and proximal LCA between aorta and pulmonal artery. There was an acute angle take off of RCA from aorta. Inter-arterial course and acute angle take off of coronary artery from aorta result in kinking and narrowing of coronary artery that contributes to myocardial infarction. There is a mismatch between myocardial demand which is increased during exertion and myocardial oxygen delivery that decreased during exertion. A surgical anterior pulmonal transposition is the suggested choice of therapy.